Availability and Utilization of Unprinted Education Resources for Teacher Job Performance in Rural and Urban Technical Colleges in Anambra State, Nigeria - Udochukwu Chukwunwike Asuzu (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: This study explores the availability and utilization of unprinted (non-textual) educational resources and their impact on teacher job performance in rural and urban technical colleges in Anambra State, Nigeria. Non-printed resources are vital for enhancing teaching effectiveness, particularly in technical education. However, the availability and use of these resources remain challenging, especially in rural schools. Method: A descriptive survey design was employed, with data collected from 343 randomly selected teachers across 15 technical colleges. A structured observational scale assessed the availability (≥50%) and utilization (4-point scale) of non-printed resources. Reliability was tested via a pilot study, and data were analyzed using descriptive and inferential statistics. Result: The study found that urban colleges had higher resource availability (42%) than rural ones (29.6%), but both were below NCCE standards. Utilization of these resources was low in both areas, with mean scores of 1.54 for rural and 2.07 for urban schools. Conclusion: The study concludes that inadequate resource availability and utilization, particularly in rural areas, hinder teaching effectiveness, emphasizing the need for better resource distribution. Contribution: This research highlights the resource disparities between rural and urban technical colleges, offering insights that can inform policies to improve resource allocation and enhance educational outcomes.